Development of advanced Fe-based oxygen carriers for chemical looping applications - Fan, Qianwenhao (Nanyang Technological University, 2024)
The escalating global energy demand and the associated environmental implications necessitate the development of cleaner, more sustainable energy technologies. Chemical looping combustion (CLC), a novel combustion technology that inherently separates CO2 during the combustion process, is a potential solution for carbon capture and storage (CCS). This technology leverages metal oxides, known as oxygen carriers, to transfer oxygen from an air reactor to a fuel reactor, where the fuel is combusted. The combustion of fuel occurs without direct contact with air, resulting in a pure stream of CO2 that can be easily captured and stored. The focus of this thesis is to address the challenges in developing advanced Fe-based oxygen carriers with improved activity and stability. The main results and findings are summarized as follows. 1. We successfully synthesized oxygen carriers with nominal compositions of MgO•MgFe2O4 (1M1F) and 5MgO•MgFe2O4 (3M1F) using a simple ball-milling assisted solid-state reaction. The novel formulation was developed with a hypothesis-driven synthesis method, leveraging computationally calculated phase diagrams (CALPHAD). The computationally predicted oxygen carrying capacities (OCC) were verified by CLC experiments in a packed bed. The formation of the highly disordered (Mg1/3Fe2/3)A(Mg2/3Fe4/3)BO4 solid solution substantially reduced the thermodynamic stability of the spinel phase, enhancing the reducibility of Fe3+. This promotion strategy does not sacrifice OCC for cyclic stability or reactivity, making it superior to conventional oxygen carrier designs. The study also presents a computer-aided oxygen carrier design approach that can significantly accelerate the search for optimal oxygen carrier formulations. 2. The influence of Co substitution at the B sites of SrFeO3 is investigated for the application of chemical looping air separation (CLAS). Phase pure perovskites could be obtained by a sol-gel method for B-site Co substitution by up to 75%. Thermogravimetric analysis revealed that the oxygen uptake and release performance of the materials can be effectively altered by B-site substitutional doping. All the perovskite structured oxygen carriers showed excellent cyclic stability over pressure swing cycles at 500 °C, suggesting their suitability for long-term operation. The enhanced activity can be rationalized by the enhanced activity of the TM-O bonds, which are correlated to descriptors such as Goldschmidt tolerance factor, the O 2p band center, and the degree of TM-O hybridization. 3. Two Fe2O3@Y2O3 oxygen carriers with yolk–shell nanostructures, Fe@s-Y and Fe@r-Y, were synthesized using a coating-etching method. The highly reproducible synthesis protocol allows fine-tuning of the shell morphology and porosity. The Fe@s-Y oxygen carrier exhibited a consistent oxygen carrying capacity of 3 wt% over 50 consecutive redox cycles, without any distinguishable structural degradation. The Fe@r-Y oxygen carrier initially possessed a higher reaction rate due to the enhanced mass transfer through the shell, but its cycling activity decayed slightly as a result of breakage of the relatively fragile porous yttria shell. Collectively, these studies provide a comprehensive investigation of innovative approaches to improve the performance of Fe-based oxygen carriers, and contribute to the broader effort to develop cleaner, more sustainable energy technologies.